Alternative sources of phosphorus in beet production aiming at the organic system - Pimenta, Lucas Daniel [UNESP]; Cardoso, Antonio Ismael Inacio [UNESP]; Sá, Jolinda Mércia de [UNESP] (FapUNIFESP (SciELO), 2024)
The demand for beet produced in the organic system has increased. This study aimed to evaluate the beet production with the use of different proportions of phosphorus sources. A randomized block design was used. The treatments were established in a 6 x 2 + 1 factorial arrangement, corresponding to 6 proportions of the phosphorus fertilizers Yoorin® thermophosphate (YT) and bone meal (BM) (100 % of P2 O5 with YT; 80 % of P2 O5 with YT + 20 % of P2 O5 with BM; 60 % of P2 O5 with YT + 40 % with BM; 40 % of P2 O5 with YT + 60 % with BM; 20 % of P2 O5 with YT + 80 % with BM; and 100 % of P2 O5 with BM), 2 doses of P2 O5 (180-recommended-and 360 kg ha-1) and 1 control without these phosphorusfertilizers. The plant height, number of leaves, root and shoot fresh and dry weight, transverse and longitudinal root diameter and total root yield were evaluated. The recommended fertilizer dose resulted in higher values, when compared to twice the recommendation. The proportion of 0 % of thermophosphate and 100 % of bone meal provided the highest mean values for the evaluated parameters. High phosphorus doses showed to be harmful to beet production.
Fontes alternativas de fósforo na produção de beterraba visando ao sistema orgânico
Keywords: Beta vulgaris L; bone meal; organic fertilization; thermophosphate